Historical dictionary of witchcraft - Durrant, Jonathan B. (Jonathan Bryan) (Historical dictionaries of religions, philosophies, and movements., 2012)
Covers the history of witchcraft from 1750 B.C.E. though the modern day. Includes a chronology, an introductory essay, and an extensive bibliography featuring cross-referenced entries on witch hunts, witchcraft trials, and related practices around the world.